HELPING STRUGGLING READERS TO READ: THE IMPACT OF THE CARE FOR THE NON-READERS (CRN) PROGRAM ON FILIPINO PUPILS’ READING PROFICIENCY - Maricel Tandoc Adapon; Benjamin Baguio Mangila (ETERNAL (English, Teaching, Learning and Research Journal), 2020)
This study was conducted to determine the impact of the Care for the Non-Readers Program on the reading performance of struggling readers in all elementary schools of Dumingag II District, Dumingag, Zamboanga del Sur, Mindanao, Philippines during the School Year 2016-2017. Fifty teachers and 465 parents were selected as respondents of the study. It made use of the descriptive comparative method of research with the questionnaire-checklist as data-gathering instrument. Both the descriptive and inferential statistics were used in the analysis and interpretation of data. The findings of the study revealed that both teachers and parents considered the Care for the Non-Readers Program as “Very Effective” in improving the reading performance of pupils. “Fuller Technique,” “Independent Reading,” “Directed Reading Thinking Activity,” and “Say Something” were the leading strategies applied by teachers in the implementation of the program. The majority of the pupils still belonged to the "Frustration" level. However, there was a significant improvement in pupils’ reading performance for three school years. Teachers encountered "Serious" problems in the implementation of the program, while the suggested solutions were considered as "Very Effective." Furthermore, there was no significant difference between the assessments of the two groups of respondents on the effectiveness of the CNR program.